Suriname - Lieberg, Carolyn S. (Chicago : Childrens Press, 1995)
Discusses the geography, history, government, economics, people, and culture of the smallest independent country of South America.
Includes index.
Wilson's Children.
8.3
5-8
Keywords: Surinam -- Juvenile literature; Surinam; Surinam